O cará-roxo (dioscorea trifida) como ingrediente funcional na indústria de panificação - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
The aim of this study was to evaluate the potential of purple yam (Dioscorea trifida), as possible health-promoting ingredient in bread making, in the state of Amazonas. Thus, we determined the centesimal composition, energy, and antioxidant activity of purple yam and four formulations of purple yam bread (0%, 10%, 15% and 20%). We also performed an acceptance test and microbiological analysis of the formulations 10%, 15% and 20%. The Kruskal-Wallis ANOVA revealed no significant differences for the parameters of the centesimal composition and energy of the four formulations, except for lipid. That is, in the process of purple yam bread making, an addition of purple yam in natura up to 20%, instead of wheat flour in ordinary bread (0%), can be made with no effect on the diet s energy, since their chemical composition are similar. By the DPPH method, the samples of purple yam revealed a high antioxidant activity, with values exceeding 70%. The three purple yam breads showed some antioxidant activity with the maximum values above 40%. The LPO method confirmed the antioxidant activity in purple yam and in purple yam breads. In both methods (DPPH and LPO), the antioxidant activity increased as the ratio of purple yam tubers, in substitution of wheat flour, was incorporated in the breads. The Friedman ANOVA was applied to compare the three formulations of purple yam breads; a significant difference only in the attribute color was revealed in the acceptance test. The 20% bread received the best evaluation; the more purple yam in the breads, the higher was the average score. Considering that, for the other sensory attributes, there were no preference differences detected among the breads, they can be considered approved. The results suggest the feasibility of purple yam bread consumption, and its possible use as a health-promoting food.
Keywords: Cará-roxo (Dioscorea trifida); Atividade antioxidante; Alimento funcional; Amazônia; Purple yam (Dioscorea trifida); Antioxidant activity; Health-promoting food; Amazonia; CIÊNCIA E TECNOLOGIA DE ALIMENTOS: CIÊNCIA DE ALIMENTOS